RANCANG BANGUN DAN PENGARUH KEPADATAN TRAFFIC TERHADAP SISTEM PENGAMAN PINTU PADA SHELTER BASE TRANCEIVER STATION (BTS) BERBASIS ANDROID - Teguh Aji Suryanto . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Telecommunications developments are accelerating, is evident from the increase in cellular-based communication tools or called by handphone. One of the main components of mobile telecommunications is a Base Transceiver Station (BTS). Shelter BTS built scattered in a network area, have a short long distance , so it requires Android based remote monitoring. In this research will be testing the response time of the hardware to the Android App. In this study using an Arduino Uno R3 as a microcontroller, GSM / GPRS Shield as a modem and use a limit switch sensor as a detector open and close the shelter door. While the application is used in the Arduino IDE and Android Studio. The test results and a discussion of test results obtained the average value of the response time is 6.4 seconds and proved to be faster than a safety device that is currently owned by PT. Hutchison 3 Indonesia Branch Pontianak. In this test performed 10 times at the weekend and workday and proven by statistical analysis using ANOVA single factor. The results of data processing by these statistics showed that the network traffic affect the duration of the response time. Key Words : Response Time, Arduino Uno R3, Arduino IDE, Android Studio, JAVA, ANOVA single factor